1998
DOI: 10.1097/00005110-199811000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Physical Restraint Use in the Acute Care Setting

Abstract: Nurse executives usually have the principal responsibility to respond to the national movement to reduce physical restraint use in hospitals. The results of this three-site, interdisciplinary, prospective incidence study (based on more than 49,000 observations collected on 18 randomly selected days) reveal new patterns in the rationale and types of restraints used. The authors discuss how the results can be used in measuring success and allocating resources for restraint reduction programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 8 publications
7
88
1
4
Order By: Relevance
“…2,[10][11][12][13] In previous studies, 2,10 the frequency of physical restraint was estimated by using surveys, a method that may be subject to bias. In observational studies [11][12][13][14] in which patients were individually examined, few different centers or ICUs were included. A recent French investigation 10 indicated that in 82% of ICUs, physical restraint was used at least once during mechanical ventilation in more than 50% of the patients.…”
mentioning
confidence: 99%
“…2,[10][11][12][13] In previous studies, 2,10 the frequency of physical restraint was estimated by using surveys, a method that may be subject to bias. In observational studies [11][12][13][14] in which patients were individually examined, few different centers or ICUs were included. A recent French investigation 10 indicated that in 82% of ICUs, physical restraint was used at least once during mechanical ventilation in more than 50% of the patients.…”
mentioning
confidence: 99%
“…Physical restraints are indicated for patient safety and avoiding falls, but the most widespread reason is to put off the taking away of invasive tubes and devices (Fletcher, 1996;Cruz et al, 1997;Minnick et al, 1998;Happ, 2000;Choi and Song 2003). Patients might need repeatedly to be self-extubated while patients was physically restrained (Balon 2001) and restrained patients of self-extubation rate were 77% (Birkett et al, 2005) .…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…The most common restraint devices are wrist restraints (Minnick et al, 1998, Happ, 2000, ankle restraint (Demir, 2007a) and chest or waist restraints (Carrion et al, 2000;Demir, 2007a). Boxing gloves or mittens, involved wrapping the hands in bandages to prevent free use of the fingers (Fletcher, 1996;Nirmalan et al, 2004), therefore preventing the patient from grabbing and pulling at tubes and lines (Demir, 2007a), are also popular.…”
Section: The Use Of Physical Restraint In Critical Carementioning
confidence: 99%
“…nick, Mion, Leipzig, Lamb, & Palmer, 1998), 우리나라의 경 우도 일반병동에서는 3.5%, 중환자실에서는 33.8%의 환자가 억제대를 사용하는 것으로 나타났다 (Kim et al, 2000).…”
unclassified